2015
DOI: 10.1002/hrm.21773
|View full text |Cite
|
Sign up to set email alerts
|

Is Competition Engaging? Examining the Interactive Effects of Goal Orientation and Competitive Work Environment on Engagement

Abstract: Contemporary work environments are growing increasingly competitive. However, some employees may "fi t" with such environments better than others. This study examined how the relationship between employees' goal orientations (learning, proving, and avoidance) and engagement is infl uenced by the competitive environment of their workplace. By investigating the interactive effect of goal orientation and competitive work environment, this research expands our understanding of factors leading to engagement. We te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 87 publications
(189 reference statements)
4
76
1
1
Order By: Relevance
“…LGO and work engagement (Adriaenssens et al, 2015;Jones et al, 2017), this study showed that a partial indirect path also exists in the relationship. The results suggest that individuals with high learning goals are engaged in their work not only because they are intrinsically motivated to acquire knowledge or skills but also because they are eager to redesign their jobs toward more challenging ones.…”
Section: Theoretical Implicationssupporting
confidence: 49%
See 1 more Smart Citation
“…LGO and work engagement (Adriaenssens et al, 2015;Jones et al, 2017), this study showed that a partial indirect path also exists in the relationship. The results suggest that individuals with high learning goals are engaged in their work not only because they are intrinsically motivated to acquire knowledge or skills but also because they are eager to redesign their jobs toward more challenging ones.…”
Section: Theoretical Implicationssupporting
confidence: 49%
“…Accordingly, previous research has indicated that individuals holding a learning goal view challenging tasks as opportunities to learn, whereas individuals holding a performance goal perceive challenging tasks as inherently risky because they fear that they might fail and reveal their inadequate abilities to others (Dragoni et al, 2009). Consistent with this argument, Adriaenssens et al (2015) and Jones et al (2017) reported a positive relationship between LGO and work engagement. Although some studies demonstrate that performance-prove and performance-avoid orientations have positive effects on performance outcomes, the results were mixed and unclear (e.g.…”
Section: Work Engagementmentioning
confidence: 78%
“…These increases are in turn linked to voice, which can be viewed as an improvement‐oriented behavior intended to help the organization. LGO is the extent to which one is motivated to master new skills and knowledge (Elliot & Dweck, ; Seijts, Latham, Tasa, & Latham, ), and has attracted growing attention from HR practitioners (De Clercq, Rahman, & Belausteguigoitia, ; Jones, Davis, & Thomas, ; London & Sessa, ). LGO precisely captures employees' interest in long‐term improvement.…”
Section: Introductionmentioning
confidence: 99%
“…LGO is the extent to which one is motivated to master new skills and knowledge (Elliot & Dweck, 1988;Seijts, Latham, Tasa, & Latham, 2004), and has attracted growing attention from HR practitioners (De Clercq, Rahman, & Belausteguigoitia, 2017;Jones, Davis, & Thomas, 2017;London & Sessa, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In short, individuals are posited to regulate their trait‐ or perception‐based competitive concerns through the adoption and pursuit of performance‐approach and performance‐avoidance goals. Several studies have provided empirical support for links between trait competitiveness and both performance‐approach and performance‐avoidance goals (Baranik, Barron, & Finney, ; Baranik, Stanley, Bynum, & Lance, ; Elliot, Al‐Dhobaiban, Kobeisy, et al, ; Harackiewicz, Durik, Barron, Linnenbrink‐Garcia, & Tauer, ; Murayama & Elliot, ; Pastor, Barron, Miller, & Davis, ; Tanaka & Yamauchi, ), and between perceived environmental competitiveness and both performance‐approach and performance‐avoidance goals (Jones, Davis, & Thomas, ; Koul, Roy, & Lerdpornkulrat, ; Lochbaum, Jean‐Noel, Pinar, & Gilson, ; Midgley & Urdan, ; Murayama & Elliot, ; Papaioannou, Ampatzoglou, Kalogiannis, & Sagovits, ; Shih, ; Wolters, ; cf. Bong, ).…”
Section: Introductionmentioning
confidence: 99%